Development of The Tourism Industry Before and After The Covid Pandemic - Bakhodir Turayev; Anukrati Sharma (Procedia of Social Sciences and Humanities, 2021)
This article examines the development of the tourism industry in Uzbekistan before and after the pandemic. A detailed analysis of the development of tourism for many years before the pandemic was made. It is widely known that many travel companies, their owners, managers and employees found themselves in a very difficult situation. The authors tried to analyze and give their forecasts, as well as recommendations for the further development of the tourism industry.